SYNTHESIS OF SOME NON-PROTEIN AMINO ACIDS DERIVED FROM SPIROHYDANTOINS: SYNTHESIS OF SOME NON-PROTEIN AMINO ACIDS DERIVED FROM SPIROHYDANTOINS - Marinov, Marin; Naydenova, Emilia; Prodanova, Rumyana; Stoyanov, Neyko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This article presents a synthesis of non-protein amino acids derived from 6- and 8- substituted cyclohexanespiro-5-hydantoins, spiro(adamantane-2’,4’-imidazolidine)- 2,5-dione and 3’,4’-dihydro-2H,2’H,5H-spiro[imidazolidine-4,1’-naphthalene]-2,5-dione. The target compounds were prepared by an alkaline hydrolysis of the corresponding spirohydantoins with barium hydroxide. The products obtained were characterized by physicochemical parameters, IR , 1H and 13C NMR spectral data.